The Influence of Fiscal Decentralization, Economic Growth, and Economic Openness on the Inter-Provincial Development Disparity in Java During 2001-2017 - Wahyu Dwi Artaningtyas; Asih Sri Winarti (EKO-REGIONAL, 2020)
In general, economic growth is defined as a process which leads to the increase of per capita income of a population in a long term. Inter-region disparity in terms of economic development is a common phenomenon in a region’s economic activities. This study aims to determine the effect of economic growth, economic openness, and the degree of fiscal decentralization on development disparities between provinces in Java within 2001-2017. Panel data regression was used together with the Random Effect Model as a data analysis technique. The data used was panel data consisting of time series data from 2001-2017 and cross-sectional data covering Special Capital Region of Jakarta, West Java, East Java, Special Region of Yogyakarta, Central Java, and Banten. The results show that economic growth and fiscal decentralization significantly influence development disparity between provinces in Java while economic openness does not affect the development inequality.